Study of the Stress-strain State of Frame Structures of Tractor Trailers - Anvar A. Togaev; Abdulaziz A. Shermukhamedov (New Approaches in Engineering Research Vol. 1, 2021)
The approach for determining the stress-strain condition of the trailer frame is discussed in the article on an example of a tractor trailer with a load-carrying capacity of 4 tons.There is a comparison of the outcomes of theoretical and experimental researches. It has been determined that the deviations of maximum values of stress when driving on a road with a satisfactory tar coating are within 4%, 10% on gravel roads with worn areas, 11% on a rotary strip with ridges in height of 8-12 cm and step of 90 cm, and 9% on a deep ditch depth of 40-45 cm and width of 100-150 cm. The calculations take into account the specific road conditions of the cotton-producing countries, which occupy four categories of road sections. The proposed method of calculation of the stress-strain state of the frame gives a good agreement with the experimental data (maximum values of stress in the range 11%) and can be used in justifying the strength parameters of tractor-trailers.